Pemberdayaan Kompetensi Vokasi : Pelatihan Kreasi Produk Rumahan Bernilai Ekonomi di SMK Bina Profesi Pekanbaru - Elida Gultom; Nova Syafrina; Jeli Nata Liyas (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
Vocational education is an education that prepares students to enter the workforce, equipping students with specific and applicable skills and knowledge, so they can immediately work in relevant fields. Entrepreneurial skills are one of the skills that can connect theory with industrial practice to create graduates who are innovative, collaborative, and ready to take advantage of existing business opportunities. This Community Service (PKM) activity was carried out at SMK Bina Profesi Pekanbaru with the Theme of Empowering Vocational Competence: Training on Creating Home Products with Economic Value at SMK Bina Profesi Pekanbaru. The purpose of this service is to increase the knowledge and understanding of SMK Bina Profesi Pekanbaru students in the field of product design and packaging so as to increase students' enthusiasm and creative ideas in managing businesses and obtaining additional family income. The service activity methods used are lecture and practice methods. The results of this service activity are expected to increase the creativity and enthusiasm of SMK Bina Profesi Pekanbaru students so that they are able to create products with economic value and have an impact on the family economy.